Ecosystem Approach to Fisheries Management Status At West Kei Kecil Small Island Park, South East Maluku Regency - Abrahamsz, James; Makailipessy, Marvin M.; Thenu, Imanuel M. (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2023)
Assessment of fisheries management with an ecosystem approach (EAFM) in the TPK Kei Kecil conservation area is important to determine the actual conditions of management in the conservation area as a follow-up step for sustainable management. This study aims to analyze the status of fisheries management and efforts to improve management based on the EAFM approach. The study was conducted in 10 villages/ohoi in 4 sub-districts in Southeast Maluku district. Data collection was carried out by interviewing fishery households and institutions as well as tracing data that referred to the EAFM indicator assessment method which included 30 indicators from six domains. The management status of the TPK Kei Kecil conservation area is classified as moderate category which is obtained based on the management status per domain, respectively: a) the domain of fish resources is moderate; b) habitat/ecosystem domain is moderate; c) fishing techniques domain is moderate; d) social domain is moderate category; e) economic domain is low category; and f) institutional domain is moderate category. Recommendations for fisheries management in the conservation area of ​​TPK Kei Kecil are sought to improve the economic domain and fishing techniques, especially in indicators of asset ownership, fishermen's household income, savings ratio, fishery capacity and fishing effort, legal documents on vessel functions and sizes as well as crew certification.